Rapid and Laboratory SARS-CoV-2 Antibody Testing in High-Risk Hospital Associated Cohorts of Unknown COVID-19 Exposure, a Validation and Epidemiological Study After the First Wave of the Pandemic - O'Kelly, Brendan; McLaughlin, Ronan; O'Doherty, Roseann; Carroll, Hailey; Murray, Roisin; Dilworth, Rachel; Corkery, Laura; Cotter, Aoife G.; McGinty, Tara; Muldoon, Eavan G.; Cullen, Walter; Avramovic, Gordana; et al. (Frontiers in Medicine, 2021)
Objective: We aimed to use SARS-CoV-2 antibody tests to assess the asymptomatic seroprevalence of individuals in high-risk hospital cohorts who’s previous COVID-19 exposure is unknown; staff, and patients requiring haemodialysis or chemotherapy after the first wave. Methods: In a single Centre, study participants had five SARS-CoV-2 antibody tests done simultaneously; one rapid diagnostic test (RDT)(Superbio Colloidal Gold IgM/IgG)), and four laboratory tests (Roche Elecsys® Anti-SARS-CoV-2 IgG (RE), Abbott Architect i2000SR IgG (AAr), Abbott Alinity IgG (AAl), and Abbott Architect IgM CMIA. To determine seroprevalence, only positive test results on laboratory assay were considered true positives. Results: There were 157 participants, of whom 103 (65.6%) were female with a median age of 50 years (range 19-90). The IgG component of the RDT showed a high number of false positives (n=18), was inferior to the laboratory assays (p<0.001 RDT vs AAl/AAr, p<0.001 RDT vs RE), and had reduced specificity (85.5% vs AAl/AAr, 87.2% vs RE). Sero-concordance was 97.5% between IgG laboratory assays (RE vs AAl/AAr). Specificity of the IgM component of the RDT compared to Abbott IgM CMIA was 95.4%. Ten participants had positivity in at least one laboratory assay, seven (9.9%) of which were seen in HCWs. Two (4.1%) haematology/oncology (H/O) patients and a single (2.7%) haemodialysis (HD) were asymptomatically seropositive. Asymptomatic seroprevalence of HCWs compared to patients was not significant (p=0.105). Conclusion: HCWs (9.9%) had higher, although non-significant asymptomatic seroprevalence of SARS-CoV-2 antibodies compared to high-risk patients (H/O 4.1%, HD 2.7%). An IgM/IgG rapid diagnostic test was inferior to laboratory assays. Sero-concordance of 97.5% was found between IgG laboratory assays, RE vs AAl/AAr.